MANAJEMEN IMPLEMENTASI MODE ULUL ALBAB DALAM PENGUATAN SPIRITUALITAS ILMU UMUM DI SMP ISLAM DARUNNAJAH BANJARMANGU - Amru Setyawinta; Syamsul Ma'arif; Fatkhuroji Fatkhuroji (STKIP Pesisir Selatan, 2026)
This study aims to analyze the management of the Ulul Albab Model implementation in strengthening the spirituality of general sciences at SMP Islam Darunnajah Banjarmangu. Employing a descriptive qualitative approach, the research utilized direct observation, in-depth interviews, and netnography through the school’s official Instagram account. Data were analyzed using the interactive model of Miles, Huberman, and Saldana, encompassing data reduction, data display, and conclusion drawing. The findings reveal that the Ulul Albab Model is implemented not merely as a pedagogical strategy, but as a value-based school management paradigm that integrates dzikr (spiritual awareness), fikr (critical thinking), and amal saleh (ethical action) within the teaching of general subjects such as Science, Social Studies, and Mathematics. The successful implementation is supported by value-oriented leadership, reflective teaching practices, and a religious school culture, which collectively contribute to the enhancement of students’ discipline, moral conduct, and spiritual awareness. However, the study also identifies several constraints, including varied levels of teacher understanding, limited instructional time, and the absence of standardized instruments for evaluating spiritual values.